DESIGN OF ZAKAT PAYMENT APPLICATION AT BAITUZZAKAH FOUNDATION BASED ON ANDROID - Salman Alfarisi (Journal of Information System, Informatics and Computing, 2023)
The absence of zakat payment software has made zakat calculations at the Baituzzakah Foundation less than optimal. The main purpose of the research that the authors did was to design a mobile-based zakat payment application for the Baituzzakah Foundation, in this case using Android, where later this application can be useful for employees of the Baituzzakah Foundation to make it easier to pay professional zakat and zakat fitrah. The application that will be made can also be used when people from outside the foundation want to pay zakat to the Baituzzakah Foundation. The research method used to design an android-based zakat payment application is to use interviews, observations or observations and literature studies to obtain more detailed data. The data that has been obtained, will then be carried out by the application design process using flowcharts and pseudocode. The results of the design process will be followed by the coding stage using the Java programming language. The application that has been designed can provide a solution to Baituzzakah Foundation employees in calculating and paying their zakat, especially professional zakat and zakat fitrah.